Global Study Revolutionizes Bankruptcy Prediction: Studi Global Merevolusi Prediksi Kebangkrutan - Ervina Indah Ansari; Duwi Rahayu (Universitas Muhammadiyah Sidoarjo, 2024)
This study evaluates bankruptcy potential in food and beverage companies listed on the Indonesia Stock Exchange during 2018-2022 using four methods: Grover, Springate, Zmijewski, and Altman. Analyzing data from 31 sampled companies, the research employs descriptive quantitative methods and SPSS 26 analysis. Findings reveal varied bankruptcy predictions: Grover predicts 3 potential bankruptcies, Springate identifies 18, Zmijewski finds none, and Altman predicts 14. Notably, Zmijewski's method demonstrates superior accuracy. These results aid investors in understanding company performance and inform future financial strategies, addressing a critical need in early bankruptcy prediction for the food and beverage industry. Future research may explore additional prediction models and extend the study period to enhance predictive accuracy further. Highlight: Diverse methods: Grover, Springate, Zmijewski, Altman offer varied bankruptcy predictions. Zmijewski's accuracy: Highest accuracy among methods for bankruptcy prediction. Investor insight: Guides future financial decisions based on company performance analysis. Keywoard: Bankruptcy, Food & beverage, Stock Exchange, Analysis, Prediction.